Women of Color in Film and Using Short Film in the Classroom - Kelly, Ernece B. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This paper describes how director Spike Lee changed Hollywood's representations of African Americans in a dramatic way. He returned to traditions of early African American filmakers like Oscar Michaux by casting all-black movies. In his first film, "She's Gotta Have It", he broke with the Hollywood tradition of using a classic beauty type as his leading lady for the character Nola Darling. In a further departure, Darling's role is not a usual one for African American women in Hollywood films: she is not a servant, a doomed mulatto, a victim, nor a "glitzy ornament" snapped to the end of a man's arm. What seemed like a breakthrough for African Americans (particularly female African Americans) collapsed with the succession of "in-the-hood movies" like "Straight Out of Brooklyn,""Hangin' With the Homeboys," and "Juice" which consistently treated women as subordinates. Although women directors first gained institutional support in the 1970s, the Director's Guild of America reported in 1990 that only 5% of the movies under guild contracts were made by women. Outstanding women of color who have begun to make a name for themselves as directors include Euzan Palcy, Julie Dash, Christine Choy, Mari-Carmen de Lara, Camille Billops, and Trinh-T. Minh-ha. English teachers will find the work of these filmakers useful because previously unexplored material can be looked at from new viewpoints. Short films can be seen more than once in a class, or instructors can assign a longer film that is currently showing. (SAM)
ERIC Note: Paper presented at the Annual Meeting of the National Council of Teachers of English (83rd, Pittsburgh, PA, November 17-22, 1993).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Blacks; Ethnic Studies; Females; Film Production; Film Production Specialists; Film Study; Higher Education; African Americans -- Film Directors; Film History -- Film Viewing; Guides, Classroom -- Teacher; Historical Materials; Speeches/Meeting Papers